A Model of ESG-Transparency Index in Corporate Reporting - R. P. Bulyga; M. V. Melnik; I. V. Safonova; V. B. Gisin (Vestnik MGIMO-Universiteta, 2023)
The increasing importance of Environmental, Social, and Governance (ESG) assessments in advancing the international sustainable development agenda necessitates the disclosure of ESG reporting information by public companies. Such disclosure plays a crucial role in facilitating effective global business communication with stakeholders and enhancing the credibility of ESG transparency measurements. The primary objective of this study is to develop and validate a robust model for a business transparency index. By leveraging mathematical tools, this model quantitatively measures the level of Environmental, Social, and Governance (ESG) transparency, taking into account the requirements of stakeholders and evaluating a public company's ability to disclose comprehensive information.The research hypothesis posits that assessing ESG transparency in public company reporting based solely on the "quantity" of estimated values, while neglecting the critical factors of "quality" and "reliability," undermines the accuracy and reliability of the results. By utilizing existing mathematical tools, a business value management model is constructed, incorporating a balanced system of "quantity," "quality," and "reliability" factors present in the ESG information disclosed in public company reports.The research methodology adopts a comprehensive approach, combining logical and structural analysis, mathematical modeling, and content analysis methods. A thorough examination of the regulatory framework, international and Russian practices, and scientific research in ESG disclosure reveals the emergence of authoritative professional standards and frameworks between 2000 and 2023. These standards and frameworks play a pivotal role in shaping the disclosure of financial and non-financial information related to sustainable development in corporate reporting. However, a significant gap exists in established practices for determining ESG transparency levels. Current "transparency indices" fall short in incorporating these factors, leading to methodological incomparability and gaps in assessing the "quality" and "reliability" of estimated values.To address this gap, the authors propose a novel mathematical model for the ESG transparency index in corporate reporting. This model effectively integrates the factors of "quantity," "quality," and "reliability" within the disclosed information of public companies. Through a comparative analysis of disclosure and verification practices across various types of activities within Russian public joint-stock companies (PJSCs), the established model enables the creation of an industry rating gradation. This rating gradation assists in determining the level of information disclosure about public companies' activities, fulfilling societal (state) requirements and optimizing business objectives.